2020
DOI: 10.1177/0271678x20934071
|View full text |Cite
|
Sign up to set email alerts
|

Differential contribution of excitatory and inhibitory neurons in shaping neurovascular coupling in different epileptic neural states

Abstract: Understanding the neurovascular coupling (NVC) underlying hemodynamic changes in epilepsy is crucial to properly interpreting functional brain imaging signals associated with epileptic events. However, how excitatory and inhibitory neurons affect vascular responses in different epileptic states remains unknown. We conducted real-time in vivo measurements of cerebral blood flow (CBF), vessel diameter, and excitatory and inhibitory neuronal calcium signals during recurrent focal seizures. During preictal states,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 104 publications
(189 reference statements)
2
17
0
Order By: Relevance
“…In addition, the authors observed a slow increase of [Ca 2þ ] following repetitive seizures in astrocytic endfeet. This resulted in a stronger arteriolar constriction in the focal and perifocal tissues, which is in line with the reduced interictal vascular and neuronal activity as described by Lim et al 101 Using 2-photon [Ca 2þ ] imaging, it has been shown that seizures result in vasoconstriction of cortical penetrating arterioles. This postictal vasoconstriction in the NVU was associated with seizure-induced hypoxia.…”
Section: Microcirculation In Human Epilepsysupporting
confidence: 79%
“…In addition, the authors observed a slow increase of [Ca 2þ ] following repetitive seizures in astrocytic endfeet. This resulted in a stronger arteriolar constriction in the focal and perifocal tissues, which is in line with the reduced interictal vascular and neuronal activity as described by Lim et al 101 Using 2-photon [Ca 2þ ] imaging, it has been shown that seizures result in vasoconstriction of cortical penetrating arterioles. This postictal vasoconstriction in the NVU was associated with seizure-induced hypoxia.…”
Section: Microcirculation In Human Epilepsysupporting
confidence: 79%
“…In terms of temporal characteristics, vasodilation in the focus occurred almost immediately after seizure onset whereas preictal vasoconstriction of vessels in distal regions occurred 5.3 ± 0.5 s before seizure onset (see Figure 4). Preictal vasoconstriction was also observed in the study by Lim et al [61], and this was found to be correlated with increased excitatory and reduced inhibitory neuronal activity levels, as shown with [Ca 2+ ] 2PI.…”
Section: Neurovasculaturesupporting
confidence: 69%
“…By using 2PI, changes in blood flow were visualized, with different states of vasoconstriction and vasodilation surrounding the epileptogenic focus [59][60][61]. Preictal vasoconstriction was found to be correlated with increased excitatory and reduced inhibitory neuronal activity levels [61]. These findings indicate that excitatory and inhibitory neurons affect surrounding neurons during epileptiform activity leading to dysfunctional local inhibition, which is supportive of the aforementioned "inhibitory model" of seizure propagation.…”
Section: Two-photon Imaging In Epilepsy Researchmentioning
confidence: 60%
See 2 more Smart Citations